Low Case Finding Among Men and Poor Viral Load Suppression Among Adolescents Are Impeding Namibia's Ability to Achieve UNAIDS 90-90-90 Targets. (11th August 2018) - Agolory, Simon; de Klerk, Michael; Baughman, Andrew L; Sawadogo, Souleymane; Mutenda, Nicholus; Pentikainen, Ndumbu; Shoopala, Naemi; Wolkon, Adam; Taffa, Negussie; Mutandi, Gram; Jonas, Anna; Mengistu, Assegid Tassew; et al.
Abstract: Background: In 2015, Namibia implemented an Acceleration Plan to address the high burden of HIV (13.0% adult prevalence and 216 311 people living with HIV [PLHIV]) and achieve the UNAIDS 90-90-90 targets by 2020. We provide an update on Namibia's overall progress toward achieving these targets and estimate the percent reduction in HIV incidence since 2010. Methods: Data sources include the 2013 Namibia Demographic and Health Survey (2013 NDHS), the national electronic patient monitoring system, and laboratory data from the Namibian Institute of Pathology. These sources were used to estimate (1) the percentage of PLHIV who know their HIV status, (2) the percentage of PLHIV on antiretroviral therapy (ART), (3) the percentage of patients on ART with suppressed viral loads, and (4) the percent reduction in HIV incidence. Results: In the 2013 NDHS, knowledge of HIV status was higher among HIV-positive women 91.8% (95% confidence interval [CI], 89.4%–93.7%) than HIV-positive men 82.5% (95% CI, 78.1%–86.1%). At the end of 2016, an estimated 88.3% (95% CI, 86.3%–90.1%) of PLHIV knew their status, and 165 939 (76.7%) PLHIV were active on ART. The viral load suppression rate among those on ART was 87%, and it was highest among ≥20-year-olds (90%) and lowest among 15–19-year-olds (68%). HIV incidence has declined by 21% since 2010. Conclusions: With 76.7% of PLHIV on ART and 87% of those on ART virally suppressed, Namibia is on track to achieve UNAIDS 90-90-90 targets by 2020. Innovative strategies are needed to improve HIV case identification among men and adherence to ART among youth.